Gambaran Penyakit Komplikasi pada Pasien Diabetes di RSUD Kardinah Kota Tegal - Meliyana Perwita Sari; Anggy Rima Putri; Nanang Kurnia Achmadi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Diabetes Mellitus is called the silent killer because this disease can affect all organs of the body and cause various kinds of complaints. Diseases that will be caused include eye vision, cataracts, heart disease, kidney disease, sexual impotence, wounds that are difficult to heal and rot / gangrene, lung infections, vascular disorders, strokes, and so on. The purpose of this study was to determine the description of complications in diabetic patients in Outpatient Hospital Kardinah, Tegal City. This research is a descriptive observation study using a cross sectional design. Data retrieval is done by means of total sampling and collecting patient data retrospectively using secondary data in the form of medical records for the period October - December 2017 taken at Outpatient Hospital Kardinah, Tegal City. The highest percentage of characteristics of diabetic patients with sex complications was 55.1%. While most complications suffered by patients with diabetes with complications are diabetic patients with other complications (other diseases and more than one complication). The most widely used antidiabetic group is metformin with a percentage of 88.8%.Keywords—Complications of disease, diabetes millitus, antidiabetic drugs